Characterization and Source Apportionment of Airborne Particulate Matter in Some Urban Neighbourhoods of Accra, Ghana - Hughes, A.F. (University of Ghana, 2014)
A year-long campaign which accounted for seasonal differences have been conducted to examine the levels, chemical composition and sources of ambient particulate matter in multiple neighbourhoods of varying socio-economic status in Accra, Ghana. Between September 2007 and August 2008, simultaneous measurements of PM2.5 and PM10 aerosols at five monitoring sites in four neighbourhoods (Asylum Down, East Legon, Nima and James Town/Ussher Town) were done for one 48-hour period every six days. Harvard Impactor with polytetrafluorethylene (PTFE) Teflon filter of 37 mm supported by a Whatman drain disc were used to sample air particles in the Accra neighbourhoods. Gravimetric analysis and energy dispersive X-ray fluorescence (EDXRF) were used to determine the chemical composition and concentration of the aerosol particles. The mean mass concentration values for PM2.5 obtained at the five sites during the study period varied from 45.9 μg m-3 to 74.8 μg m-3. The mean mass concentration for PM10 also varied from 93.9 μg m-3 to 134.8 μg m-3. These levels were all substantially higher than the EPA (Ghana) guidelines values and other international air quality standards from WHO, USEPA and EU. Weak relationships were obtained between PM and weather parameters. Crustal elements were most abundant during the seasonal Harmattan period between late December and early February when Saharan dust is transported across West Africa. Enrichment factor analysis was used to provide an initial indication of the species of anthropogenic origin in the measured elemental composition. Source contributions were analysed using positive matrix factorization (PMF) model separately for Harmattan and non-Harmattan periods because large changes to source profiles is expected during the Harmattan period. Anthropogenic sources resolved by PMF model (biomass burning, solid waste burning, resuspended dust and traffic/industry emissions) during both Harmattan and non-Harmattan periods had significant influence on the four neighbourhoods in Accra.
Thesis (PhD) - University of Ghana,2014